PENDEKATAN PEMBELAJARAN BAHASA INDONESIA BAGI PENUTUR ASING (BIPA) BERBASIS BUDAYA SERUMPUN DI FILIPINA - Ida Yeni Rahmawati; Nuraini Nuraini; Rizal Arifin; Subangun Subangun; Raya Nurlianharkah (IKIP PGRI Bojonegoro, 2023)
Abstract: Indonesian is one of the foreign languages studied by students and people in the Philippines. Throughout 2022 alone, the Indonesian Embassy in Manila, Philippines has been flooded with students and institutions wishing to work with Indonesia to organize Indonesian language classes. The enthusiasm of Filipino students certainly wants to be welcomed by learning Indonesian which is certainly able to accommodate the needs of students. Basically this learning, apart from being able to accommodate the needs of students, should also be inseparable from efforts to diplomacy Indonesian language and culture. Of course there are still many other foreign languages that compete with Indonesian in the Philippines. The purpose of this study is to describe and explain the existence of Indonesian language teaching in the Philippines based on cognate culture. The research method used is using a qualitative descriptive method. The collection of data used is using observation, interviews, and documentation. The wettability of the data in this study uses source triangulation. Meanwhile, the results of this study are that with the similarities in both cultural and linguistic aspects that are still allied, it makes students more enthusiastic in deepening Indonesian. Keywords: BIPA Learning, Diplomacy, Allied Culture, Philippines Abstrak: Bahasa Indonesia merupakan salah satu bahasa asing yang dipelajari mahasiswa dan masyarakat di Filipina. Sepanjang tahun 2022 saja, KBRI Manila, Filipina dibanjiri pemelajar maupun lembaga yang ingin bekerjasama dengan Indonesia untuk menyelenggarakan kelas bahasa Indonesia. Antusias pemelajar Filipina ini tentu hendak disambut dengan pembelajaran bahasa Indonesia yang tentu mampu mengakomodasi kebutuhan pemelajar. Pada dasarnya pembelajaran ini selain mampu mengakomodir kebutuhan pemelajar, hendaknya juga tidak terlepas dengan upaya diplomasi kebahasaan maupun kebudayaan Indonesia. Bahasa asing lainnya tentu masih banyak yang bersaing dengan bahasa Indonesia di Filipina. Tujuan dari penelitian ini ialah untuk mendeskripsikan dan menjelaskan mengenai eksistensi pengajaran bahasa Indonesia di Filipina berbasis budaya serumpun. Metode penelitian yang digunakan ialah menggunakan metode deskriptif kualitatif. Pengumpulan data yang digunakan ialah menggunakan pengamatan, wawamcara, dan dokumentasi. Kebasahan data dalam penelitian ini menggunakan triangulasi sumber. Sedangkan, hasil dari penelitian ini ialah dengan adanya kemiripan baik dari aspek budaya maupun bahasa yang masih serumpun, maka membuat pemelajar semakin antusias dalam memperdalam bahasa Indonesia. Kata Kunci: Pembelajaran BIPA, Diplomasi, Budaya serumpun, Filipina